Downside Variance Risk Premium - Bruno Feunou; Mohammad R. Jahan-Parvar; Cédric Okou (Bank of Canada, 2015)
We decompose the variance risk premium into upside and downside variance risk premia. These components reflect market compensation for changes in good and bad uncertainties. Their difference is a measure of the skewness risk premium (SRP), which captures asymmetric views on favorable versus undesirable risks. Empirically, we establish that the downside variance risk premium (DVRP) is the main component of the variance risk premium. We find a positive and significant link between the DVRP and the equity premium, and a negative and significant relation between the SRP and the equity premium. A simple equilibrium consumption-based asset pricing model supports our decomposition.
Keywords: G1; G12; 330; Asset pricing